2020
DOI: 10.3390/cancers12061616
|View full text |Cite
|
Sign up to set email alerts
|

How and Why Are Cancers Acidic? Carbonic Anhydrase IX and the Homeostatic Control of Tumour Extracellular pH

Abstract: The acidic tumour microenvironment is now recognized as a tumour phenotype that drives cancer somatic evolution and disease progression, causing cancer cells to become more invasive and to metastasise. This property of solid tumours reflects a complex interplay between cellular carbon metabolism and acid removal that is mediated by cell membrane carbonic anhydrases and various transport proteins, interstitial fluid buffering, and abnormal tumour-associated vessels. In the past two decades, a convergence of adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 162 publications
0
74
0
Order By: Relevance
“…This is because the targets, CA IX/CA XII are only expressed within the hypoxic niches of solid tumors and may represent a minor portion of the total tumor cell population. However, these hypoxic cells have the properties for self-renewal [ 159 , 160 , 161 ], migration/invasion [ 162 , 163 , 164 ], and survival in an acidic tumor microenvironment [ 163 , 164 , 165 , 166 , 167 , 168 ] and significantly contribute to resistance to chemo-, radiation, and immunotherapies. Thus, CA IX/CA XII inhibitors are not likely to have a major effect on tumor growth and metastasis by themselves as mono-therapeutics but need to be used in combination with chemo-, radiation-, and immunotherapies to eliminate resistant populations and for maximum durable suppression of tumor growth and metastasis.…”
Section: In Vivo Studies Preclinical and Clinical Trials Of Ca IXmentioning
confidence: 99%
“…This is because the targets, CA IX/CA XII are only expressed within the hypoxic niches of solid tumors and may represent a minor portion of the total tumor cell population. However, these hypoxic cells have the properties for self-renewal [ 159 , 160 , 161 ], migration/invasion [ 162 , 163 , 164 ], and survival in an acidic tumor microenvironment [ 163 , 164 , 165 , 166 , 167 , 168 ] and significantly contribute to resistance to chemo-, radiation, and immunotherapies. Thus, CA IX/CA XII inhibitors are not likely to have a major effect on tumor growth and metastasis by themselves as mono-therapeutics but need to be used in combination with chemo-, radiation-, and immunotherapies to eliminate resistant populations and for maximum durable suppression of tumor growth and metastasis.…”
Section: In Vivo Studies Preclinical and Clinical Trials Of Ca IXmentioning
confidence: 99%
“…Tumors display considerable metabolic heterogeneity and produce a considerable fraction of their energy not only by glycolysis, but also from oxidation in the TCA (for review see [ 51 , 52 , 53 ]). Therefore, CO 2 is a significant source of metabolic acid production also in cancer cells [ 54 ]. However, the mere release of metabolic acids alone does not suffice to fully describe the low pH e values found in solid tumors.…”
Section: Carbonic Anhydrases In Cancer Cellsmentioning
confidence: 99%
“…Furthermore, CAs have been suggested to serve as therapeutic targets in the treatment of neuropathic pain [ 157 ] and obesity [ 158 ]. In solid tumors, the acidic tumor environment, which is created by CAIX catalytic activity, provides a potential target for cancer therapy, since it is a unique feature for solid tumors and a common phenotype of a wide spectrum of cancer types [ 54 ]. Indeed, various preclinical studies have shown that CA inhibitors like acetazolamide derivates, glycosyl coumarins, or the ureido-substituted benzenesulfonamide SLC-0111 can inhibit tumor growth, formation of metastasis, and reverse malignancy in cultured cancer cells, in spheroids and in tumor xenografts [ 159 , 160 , 161 , 162 ].…”
Section: Targeting Transport Metabolons For Cancer Therapymentioning
confidence: 99%
“…[ 156 ] This mechanism could be particularly effective for targeted therapeutic delivery for cancer treatment where microrobots loaded with anticancer agents are guided toward the cancerous tumors which are known to be acidic in nature. [ 157 ] Chemotaxis can also be used in immunotherapy where microrobots loaded with immune cells are delivered to the vicinity of the target lesion and the loaded cells are naturally released by a chemotaxis response.…”
Section: Concluding Remarks Toward Clinical Translationmentioning
confidence: 99%